1991
DOI: 10.1164/ajrccm/144.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Albuterol Inhalation on the Work of Breathing during Weaning from Mechanical Ventilation

Abstract: The work of breathing is a major determinant of the success of weaning from mechanical ventilation. The aim of this study was to assess whether an inhaled bronchodilator could reduce the mechanical load on the respiratory muscles and diminish the work. For this purpose, 15 intubated patients in the process of weaning from mechanical ventilation inhaled the beta 2-agonist bronchodilator albuterol via a spacer device filled with 1 mg of the drug and connected to the endotracheal tube. During spontaneous breathin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
6

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 5 publications
0
27
1
6
Order By: Relevance
“…Inspiratory work of breathing was found to decrease in 9 out of 10 mechanically-ventilated patients following nebulization of 1.8 mg of metaproterenol [56]. This reduction may help in weaning problem patients from mechanical ventilation [40]. In 15 intubated patients, MANCEBO et al [40] found a significant reduction in inspiratory work of breathing after administration of 10 puffs of albuterol with a MDI and spacer.…”
Section: Reduction In Hyperinflationmentioning
confidence: 97%
See 3 more Smart Citations
“…Inspiratory work of breathing was found to decrease in 9 out of 10 mechanically-ventilated patients following nebulization of 1.8 mg of metaproterenol [56]. This reduction may help in weaning problem patients from mechanical ventilation [40]. In 15 intubated patients, MANCEBO et al [40] found a significant reduction in inspiratory work of breathing after administration of 10 puffs of albuterol with a MDI and spacer.…”
Section: Reduction In Hyperinflationmentioning
confidence: 97%
“…This reduction may help in weaning problem patients from mechanical ventilation [40]. In 15 intubated patients, MANCEBO et al [40] found a significant reduction in inspiratory work of breathing after administration of 10 puffs of albuterol with a MDI and spacer. This decrease was largely due to a marked reduction in lung and airway resistance.…”
Section: Reduction In Hyperinflationmentioning
confidence: 99%
See 2 more Smart Citations
“…These "flow-by" or flow-triggered mechanisms have been compared to conventional demand-valve systems, and recent studies [58][59][60] have reported that flow-by systems, used either in CPAP or SIMV, are able to produce a significant decrease in respiratory work and other indices of inspiratory muscle effort when compared to the conventional demand-valve.…”
Section: Spontaneous Breathing With T-tubementioning
confidence: 99%